The utilization of the multimodal immunotherapy for the opsoclonus–myoclonus syndrome can reduce relapses and permanent neurological sequelae - Fang He; Miriam Kessi; Ciliu Zhang; Jing Peng; Fei Yin; Lifen Yang (Italian Journal of Pediatrics)
Abstract Background There is no known effective treatment strategy to prevent relapses and avert permanent neurological sequelae in opsoclonus–myoclonus syndrome (OMS). To describe the treatment strategy that reduced relapses and led to remission of OMS without permanent neurological sequelae. Methods This cross-sectional study was conducted at the Department of Pediatrics, Xiangya Hospital, Central South University. Patients diagnosed with OMS from January 2014 to July 2022 were enrolled. Exposures included treatment with multimodal immunotherapy. Main outcomes and measures included the OMS severity grading scale and DQ/IQ scores. The clinical data was collected and analysed. Results Of the six recruited patients, three were (50.00%) males. The median age of onset was 15.50 months. Preceding manifestation was present in one patient and two cases had neuroblastoma. The mean duration from disease onset to the initiation of therapies was 1.86 months. The combinations of ≥ two therapies were used: combination of the intravenous immunoglobulin (IVIG) plus intravenous dexamethasone plus rituximab was used for three (50.00%) patients and the combination of the IVIG plus intravenous dexamethasone plus rituximab plus mycophenolate mofetil for one (16.67%) case. Besides, the combination of the intravenous methylprednisolone (IVMP, which was switched to intravenous dexamethasone later) plus rituximab was utilized for one (16.67%) case and the combination of the IVIG and IVMP for one (16.67%) patient. Total numbers of the therapies used comprised of dual therapy (33.33%), triple therapy (50.00%), and other multiple agents (16.67%). Besides, surgical resections were done for the cases with tumors. The disease course was monophasic for five cases and five cases achieved remission. OMS scores improved significantly at the end of follow up. Five (83.33%) patients did not have permanent neurological sequelae. Conclusions The combination of the intravenous dexamethasone plus IVIG plus rituximab for the OMS can reduce relapses and permanent neurological sequelae.